If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(y + -1) * dx + -1y(x + -1) * dy = 0 Reorder the terms: x(-1 + y) * dx + -1y(x + -1) * dy = 0 Reorder the terms for easier multiplication: x * dx(-1 + y) + -1y(x + -1) * dy = 0 Multiply x * dx dx2(-1 + y) + -1y(x + -1) * dy = 0 (-1 * dx2 + y * dx2) + -1y(x + -1) * dy = 0 (-1dx2 + dx2y) + -1y(x + -1) * dy = 0 Reorder the terms: -1dx2 + dx2y + -1y(-1 + x) * dy = 0 Reorder the terms for easier multiplication: -1dx2 + dx2y + -1y * dy(-1 + x) = 0 Multiply y * dy -1dx2 + dx2y + -1dy2(-1 + x) = 0 -1dx2 + dx2y + (-1 * -1dy2 + x * -1dy2) = 0 Reorder the terms: -1dx2 + dx2y + (-1dxy2 + 1dy2) = 0 -1dx2 + dx2y + (-1dxy2 + 1dy2) = 0 Reorder the terms: -1dxy2 + -1dx2 + dx2y + 1dy2 = 0 Solving -1dxy2 + -1dx2 + dx2y + 1dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(-1xy2 + -1x2 + x2y + y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(-1xy2 + -1x2 + x2y + y2)' equal to zero and attempt to solve: Simplifying -1xy2 + -1x2 + x2y + y2 = 0 Solving -1xy2 + -1x2 + x2y + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add 'xy2' to each side of the equation. -1xy2 + -1x2 + x2y + xy2 + y2 = 0 + xy2 Reorder the terms: -1xy2 + xy2 + -1x2 + x2y + y2 = 0 + xy2 Combine like terms: -1xy2 + xy2 = 0 0 + -1x2 + x2y + y2 = 0 + xy2 -1x2 + x2y + y2 = 0 + xy2 Remove the zero: -1x2 + x2y + y2 = xy2 Add 'x2' to each side of the equation. -1x2 + x2y + x2 + y2 = xy2 + x2 Reorder the terms: -1x2 + x2 + x2y + y2 = xy2 + x2 Combine like terms: -1x2 + x2 = 0 0 + x2y + y2 = xy2 + x2 x2y + y2 = xy2 + x2 Add '-1x2y' to each side of the equation. x2y + -1x2y + y2 = xy2 + x2 + -1x2y Combine like terms: x2y + -1x2y = 0 0 + y2 = xy2 + x2 + -1x2y y2 = xy2 + x2 + -1x2y Add '-1y2' to each side of the equation. y2 + -1y2 = xy2 + x2 + -1x2y + -1y2 Combine like terms: y2 + -1y2 = 0 0 = xy2 + x2 + -1x2y + -1y2 Simplifying 0 = xy2 + x2 + -1x2y + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| -143+10x=4x+49 | | 16d^2=-64d | | x+y+2x+2=39 | | -4(-6x+3)=-3x | | 5x+5x+3=32 | | 11x+7=15x-5 | | 6x^3+3x^3=18x | | x+3*4=9 | | 20x+11=360 | | -138-4x=192+11x | | x(x+3)=35 | | -2.67x-8.4=6.072+0.03x | | y=(-0.25)x+50 | | -230+2x=19+3x | | (t+z)=45z+67 | | g(X)=x-3+2 | | 2d-4=-3 | | 6x-15+4x+8=3x+9+7x-16 | | 3x+20=1500 | | 2g+7=15 | | -11+2x=19+3x | | 24x+11=123 | | -20+13x=22+11x | | 3c+2p=78 | | X-9=-3+8 | | 2b+1=-9 | | 2*-1.6+6y=-12 | | -3(7m+4)=20-5m | | 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A |